Pemanfaatan Limbah Bongol Jagung Untuk Pembuatan arang Briket Sebagai Upaya Mensukseskan Program Zero Waste - Dedi Supriadi; Junaidi; Syukron Anshori (Forum Kerjasama Pendidikan Tinggi, 2024)
Sumbawa Regency has great potential in agricultural waste management, the use of corn cob waste as raw materials for making charcoal briquettes. The use of corn cob waste is an innovative step in supporting the Sumbawa Regency Regional Government program, namely zero waste. The purpose of this activity is to educate and train the Partner Institution of the Olat Maras Social Welfare Institute (LKSOM) and the Pernek Village Government of Sumbawa Regency to be fair in reducing the heating of Gelobal due to the burning of corn bongol waste. The implementation method in this activity is a Focus group discussion (FGD) between Lecturers of Sumbawa University of Technology (UTS) and Partner Institutions. The process is carried out through the stages of observation, socialization of training and publication. The results obtained are the existence of charcoal briquette products made from corn cob waste. The charcoal briquettes produced have physical characteristics that are quite ideal for its use as an alternative fuel. The physical shape of charcoal briquettes is in the form of a cylinder with a height of about 3 cm and a diameter of about 5 cm and is quite hard with a starch adhesive type with a percentage of 5%, and 10% respectively. The results of the tests that have been carried out conclude that the test process of igniting briquettes into coals that are ready to be used only takes one minute. This innovation is expected to be a model for other regions in managing agricultural waste in a sustainable and efficient manner. This service program is fully funded by the Ministry of Education, Culture, Research and Technology through the BIMA application.